The Influences of Work Environment, Workload, and Job Stress on Turnover Intention in PT Indofood CPB Sukses Makmur of Noodle Division - Farezha Putri, Iona; Wijayanto, Petrus (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
PT Indofood CBP Sukses Makmur of Noodle Division always tries to improve its human resources' welfare. This study aims to examine the influence of work environment, work stress, and workload on turnover intention at PT Indofood Sukses Makmur Tbk Semarang, particularly regarding the influence of work environment relationships, work stress, and workload on employee turnover intention. This research used quantitative approach. The sample in this study involved 45 employees of PT Indofood CBP Sukses Makmur of Noodle Division Semarang. The analysis used multiple linear analysis. The results revealed that there are some influences between the work environment variable (X1), workload variable (X2), and the work stress load variable (X3) on the turnover intention variable (Y).